Evaluation of the quality of primary care health services in 37 municipalities in the State of Sao Paulo, Brazil: organizational dimensions of care - Castanheira, Elen Rose L.; Dalben, Ivete; Almeida, Margareth A. Santini de; Puttini, Rodolfo Franco; Patrício, Karina Pavão; Machado, Dinair Ferreira; Caldas Júnior, Antonio Luis; Nemes, Maria Inês Battistella (Saúde e Sociedade, 2009)
The State of São Paulo, Brazil, has a broad network of primary health care services (PHCS) whose organizational profile is heterogeneous and not well known. This study analyzes the organization of PHCS in 37 municipalities located in the central-west region of São Paulo, as the first part of a broader project that evaluates the quality of these services. This is a cross-sectional study conducted through a structured questionnaire answered by the local managers and health teams. The questions addressed institutional characteristics and the organization and management of the work process. The questionnaires were sent to 131 UBS (Primary Health Care Units) distributed across 37 municipalities. There were responses from 113 units (87%) located in 32 municipalities (86.4%). Of the overall number of units, 57 (50%) are traditional UBS, 26 (22.8%) are family health units, and 31 (27.2%) are mixed. Most services (62%, 70/113) do not work with catchment areas delimited in a planned way. Services are divided between those who perform 70% to 100% of scheduled medical consultations (37.6%, 41/109) and those who perform 70% to 100% of non-scheduled consultations (39.4%, 43/109). Sixty-five units (63.7%, 65/102) do not have community-based committees. Based on the collected data, it is possible to discuss the main features of the health programs, procedures and activities carried out by PHCS. The predominant organizational profiles reveal deficiencies of structure and process in relation to the guidelines issued by SUS (Brazil's National Health System). The development of self-assessment instruments allows the teams to appropriate their work in a critical way and to carry out new technological arrangements to improve the quality of the care provided.